Results of the valve-preserving operations in the patients, suffering aortal dissection Type A - V. I. Kravchenko; I. M. Kravchenko; O. O. Lohvinenko; V. V. Lazoryshynets (Клінічна хірургія, 2020)
Objective. To investigate resuspension of aortal valve in the patients, suffering aortal dissection of Type A.